THE INFLUENCE OF MARKETING MIX TO PATIENT SATISFACTION IN HOSPITALS: NARRATIVE REVIEW - Batubara, Nurul Qosimah; Wibowo, Adik (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Hospitals, as service providers, have a large role in meeting people's needs regarding their health. The increasing growth of hospitals adds to the menu of choices for people to utilize health services according to their needs. This competition has changed the mechanism by which customers are not only users of health services but as determinants of the future and the continuity of a hospital. Marketing activities can help hospitals improve and win the competition. Marketing managers must be able to combine the marketing mix variables appropriately so that all variables can increase consumer's decision and patient satisfaction.  Aims. The purpose of this study was to determine the effect of mix marketing on patient satisfaction at the hospital. Method: This study was conducted in a literature review by searching for articles and journals related to hospital mix marketing. Search journal articles are done through Google Scholar database with the search year 2010 until 2018. The keywords used are "marketing mix and "hospital." So that six articles will be reviewed.  Results: In the six studies reviewed there was one study that showed that all the mix marketing variables namely product, price, people, place, promotion, process, and the physical evidence had a significant influence on patient satisfaction and the hospital for medical treatment. The significant results are known from the results of statistical tests showing that p-value <0.05. In several other studies, it shows that there are significant variables and some that are not significant for consumer decision and patient satisfaction.   Conclusion: The Marketing mix has an important cost for the decision to choose a hospital. The mix marketing has varied significant influence on consumers? decision and satisfaction to choose the hospital for medical treatment. By knowing the mix marketing variable that affects customer satisfaction, hospital management, namely the marketing department, can optimize and develop marketing types that can increase public interest so that the target profit of the hospital is achieved.